Reducing the Weight of Spinal Pain in Children and Adolescents - Thorvaldur S. Palsson; Alessandro Andreucci; Christian Lund Straszek; Michael Skovdal Rathleff; Morten Hoegh (MDPI AG, 2021)
Spinal pain in adults is a significant burden, from an individual and societal perspective. According to epidemiologic data, spinal pain is commonly found in children and adolescents, where evidence emerging over the past decade has demonstrated that spinal pain in adults can, in many cases, be traced back to childhood or adolescence. Nevertheless, very little focus has been on how to best manage spinal pain in younger age groups. The purpose of this article is to put the focus on spinal pain in children and adolescents and highlight how and where these problems emerge and how they are commonly dealt with. We will draw on findings from the relevant literature from adults to highlight potential common pathways that can be used in the management of spinal pain in children and adolescents. The overall focus is on how healthcare professionals can best support children and adolescents and their caregivers in making sense of spinal pain (when present) and support them in the self-management of the condition.